PENGARUH PROMOSI SOCIAL MEDIA, KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN PRODUK EATLAH DI ERA COVID 19 - Raden Rafly Danuartho Harris, (2022)
Business competition in the industrial era 4.0 and the presence of the covid 19 pandemic have resulted in many companies having to adjust their strategies so that marketing activities can run smoothly, including Eat companies, which must have an advantage in order to compete with other Food & Beverages businesses. This study aims to determine, analyze, and prove the effect of Social Media Promotion and Service Quality on purchasing decisions for Eatlah products in the Covid Era 19. The sample used in this study amounted to 100 people consisting of Eatlah consumers using a purposive sampling technique. The test equipment used in this research is SmartPLS 3.0 with a significance value of 5% or 0.05. The results of this study found that: (1) There is a positive and significant influence of social media promotion on the decision to purchase Eatlah products: (2) There is a positive and significant influence of service quality on the purchase decision of Eatlah products. The researcher suggests to other researchers to add to the types of dependent variables that influence the decision to buy Eatlah products.